2014
DOI: 10.1007/s13277-014-1704-8
|View full text |Cite
|
Sign up to set email alerts
|

The effects of STAT3 and Survivin silencing on the growth of human bladder carcinoma cells

Abstract: Despite accumulating evidence suggesting a critical role of signal transducer and activator of transcription 3 (STAT3) and Survivin in human bladder cancer, the effects of silencing these genes on the proliferation of T24 bladder carcinoma cells remain unknown. Here, we investigated the inhibitory effects of STAT3 or Survivin silencing on the in vitro and in vivo growth of human T24 bladder carcinoma cells. Small interfering RNA (siRNA) vectors targeting STAT3, Survivin, or both genes were designed and synthes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 19 publications
0
13
0
Order By: Relevance
“…Many studies have shown that Survivin could serve as a molecular target for bladder cancer therapy [3335]. Knockdown of Survivin by using siRNA could dramatically suppress the proliferation and invasion of bladder cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have shown that Survivin could serve as a molecular target for bladder cancer therapy [3335]. Knockdown of Survivin by using siRNA could dramatically suppress the proliferation and invasion of bladder cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…The (a) tumor diameter and the (b) shortest track were measured using a vernier caliper every five days. The tumor volume (in cubic millimeter) was calculated according to the formula V=ab 2 /2 (15). On day 20, the tumors were removed and weighed.…”
Section: Methodsmentioning
confidence: 99%
“…In this study, the downregulation of STAT3 or Survivin, an inhibitor of apoptosis, suppressed the proliferation of BC cells. Moreover, no additive effects were recorded by the STAT3 and Survivin joined knockdown, suggesting that they both belong to the same pathway in T24 cells [75]. …”
Section: Role Of Stat3 Signaling In Bladder Cancermentioning
confidence: 99%